2021
DOI: 10.3126/dristikon.v11i1.39154
|View full text |Cite
|
Sign up to set email alerts
|

Dyscalculia in Learning Mathematics: Underpinning Concerns for Delivering Contents

Abstract: Dyscalculia is a term that affects the ability to acquire arithmetical skills. It is one of the important areas of a specific learning disorder in mathematics covering the areas particularly, number sense, memorization of arithmetic facts, accurate and fluent calculation, and accurate math reasoning. It is estimated that about 3-6 percent of the population is facing problems associated with dyscalculia. This paper explores the theoretical consideration of dyscalculia in learning mathematics and outlines the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Thus, Dyscalculia is a developmental disorder which is detected at a specific part of the brain. It is also found that, although children diagnosed with Dyscalculia have severe educational difficulties, they can solve complicated Math problems, provided more time (Kunwar, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Dyscalculia is a developmental disorder which is detected at a specific part of the brain. It is also found that, although children diagnosed with Dyscalculia have severe educational difficulties, they can solve complicated Math problems, provided more time (Kunwar, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to mention that even Math-related words cause Anxiety to children with Dyscalculia -who do not experience Anxiety in general. Another negative impact of Dyscalculia is that it can cause dysfunction of the working memory (Kunwar, 2020;Landerl et al, 2003;Rubinstein & Tannock, 2010;Shalev, 2004;Shalev & Gross-Tsur, 2000).…”
Section: Dyscalculiamentioning
confidence: 99%
“…Calculation Difficulties:Due to brain injuries, individuals with ACD may face significant challenges in mathematical calculations ( Cohen et al, 2018 ). This includes not only complex mathematical calculations, such as solving algebraic and geometric problems, but also simpler tasks like basic arithmetic operations ( Kaufmann, 2008 ; Kunwar, 2021 ). They might make mistakes easily during calculations or take longer to complete tasks that should be simple and quick.…”
Section: Discussionmentioning
confidence: 99%
“…Calculation Difficulties:Due to brain injuries, individuals with ACD may face significant challenges in mathematical calculations (Cohen et al, 2018). This includes not only complex mathematical calculations, such as solving algebraic and geometric problems, but also simpler tasks like basic arithmetic operations (Kaufmann, 2008;Kunwar, 2021). They might make mistakes easily during calculations or take longer to complete tasks that should be simple and quick.…”
Section: Acquired Calculation Disorder (Acd)mentioning
confidence: 99%